France and Africa : an Indian perspective - Dubey, Ajay Kumar; African Studies Association of India (New Delhi : African Studies Association of India ; Delhi : Marketed and distributed by Kalinga Publications, 2009)
Contributed articles of symposium held at New Delhi.
section 1. France and Francophone Africa -- section 2. France and Af rica : implications for India -- section 3. France, India, and Francoph one Africa.
Includes bibliographical references.
Keywords: Africa, French-speaking -- Relations -- France -- Congresses; France -- Relations -- Africa, French-speaking -- Congresses; Africa, French-speaking -- Relations -- India -- Congresses